2005
DOI: 10.1086/428597
|View full text |Cite
|
Sign up to set email alerts
|

The History of the Mysterious Eclipses of KH 15D. II. Asiago, Kiso, Kitt Peak, Mount Wilson, Palomar, Tautenburg, and Rozhen Observatories, 1954-1997

Abstract: The unusual pre-main-sequence binary star KH 15D undergoes remarkably deep and long-lasting periodic eclipses. Some clues about the reason for these eclipses have come from the observed evolution of the system's light curve over the last century. Here we present UBVRI photometry of KH 15D from 1954 to 1997 based on photographic plates from various observatories. The system has been variable at the %1 mag level since at least 1965. There is no evidence of color variations, with a typical limit of Á(B À V ) < 0:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
(31 reference statements)
3
16
0
Order By: Relevance
“…1995/1996 observing season at VVO is interpreted as the point in time when the currently hidden star (B) made its last appearance. Based on this datum, we show that star B is 0.46 ± 0.03 mag brighter than the currently visible star A, which is entirely consistent with the historical light curve (Johnson et al 2005). Finally, well-sampled V J and I J data obtained at the CTIO/Yale 1-m telescope during 2001/2002 show an entirely new feature: the system becomes bluer by a small but significant amount in very steady fashion as it enters eclipse and shows an analogous reddening as it emerges from eclipse.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…1995/1996 observing season at VVO is interpreted as the point in time when the currently hidden star (B) made its last appearance. Based on this datum, we show that star B is 0.46 ± 0.03 mag brighter than the currently visible star A, which is entirely consistent with the historical light curve (Johnson et al 2005). Finally, well-sampled V J and I J data obtained at the CTIO/Yale 1-m telescope during 2001/2002 show an entirely new feature: the system becomes bluer by a small but significant amount in very steady fashion as it enters eclipse and shows an analogous reddening as it emerges from eclipse.…”
supporting
confidence: 83%
“…While Herbst et al (2002) first suggested the possibility of a binary companion, the light curve between 1967 and 1982 led JW04 to believe that the light from a second brighter star once contributed to the flux coming from this system, and that the second star is now completely obscured. These results have been confirmed and extended by data obtained at various observatories between 1954 and 1997 (Johnson et al 2005).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…A disk that is warped, precessing, or that contains overdense regions can also produce occasional and potentially deep eclipses, as in the cases of UX Ori stars ("Uxors, " Wenzel 1969;Waters & Waelkens 1998;Dullemond et al 2003) including AA Tau (Bouvier et al 2013) and V409 Tau (Rodriguez et al 2015). In the case of an inclined, warped, and/or precessing circumbinary disk, the stars' orbits might bring them behind the disk in a complex pattern, as in the case of KH 15 D (an eccentric binary star system occulted by a warped disk, Chiang & Murray-Clay 2004;Winn et al 2004;Johnson et al 2005).…”
Section: Exomoonsmentioning
confidence: 99%
“…Alternatively, and perhaps more plausibly, the period may be the orbital period of a binary star system. We imagine a system analogous to KH 15D during the 1960's-80's in which one member of a binary is obscured by a circumbinary disk during a portion of each cycle (Johnson & Winn 2004;Johnson et al 2005). As in the case of KH 15D this requires an eccentric orbit that is somewhat inclined to the plane of the circumbinary disk.…”
Section: Discussionmentioning
confidence: 99%